Physicochemical properties and lignin degradation of thermal-pretreated oil palm empty fruit bunch - Intan Nazirah Mohammad; Clarence M. Ongkudon; Mailin Misson (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
Oil palm empty fruit bunches (EFB) are recoverable lignocellulosic biomass serving as feedstock for biofuel production. The major hurdle in producing biofuel from biomass is the abundance of embedded recalcitrant lignin. Pretreatment is a key step to increase the accessibility of enzymes to fermentable sugars. In this study, thermal pretreatments at moderate temperatures ranging from 150 ◦C to 210 ◦C, at different durations (30–120 min) and EFB particle sizes (1–10 mm), were employed to maximize lignin degradation. Observation through a scanning electron microscope (SEM) revealed disruptions in EFB structure and the removal of silica bodies and other impurities upon thermal pretreatment. Remarkable changes on the elemental contents and functional groups occurred, as was evident from the energy dispersive X-ray (EDX) and Fourier transform infrared (FTIR) analyses. The smallest EFB size yielded higher lignin degradation—about 2.3-fold and 1.2-fold higher—than the biggest and moderate tested EFB sizes, indicating a smaller particle size provides a higher surface area for bioreaction. Furthermore, applying a longer duration of treatment and a higher temperature enhanced lignin degradation by up to 58%. This study suggests that moderate thermal treatment could enhance lignin degradation by altering the physicochemical structure of EFB, which is beneficial in improving biofuel production.